2011
DOI: 10.1253/circj.cj-10-1122
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Baroreflex Sensitivity to Predict Cardiac and Cerebrovascular Events in Type 2 Diabetic Patients

Abstract: Background: Cardiovascular autonomic neuropathy is a major complication in patients with diabetes mellitus (DM), and baroreflex sensitivity (BRS) reportedly can predict cardiovascular prognosis in type 2 DM patients. The hypothesis that cardiovascular events are associated with gender differences in BRS was tested in the present study. Methods and Results:From 1998, we have evaluated BRS by phenylephrine methods in 185 consecutive type 2 DM patients. The long-term prognostic value of BRS was compared between 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Studies in DM patients have demonstrated that the degree of autonomic (sympathovagal) imbalance determines the extent of BRS impairment [82]. In addition, the extent of BRS impairment is also a determinant factor as a more depressed BRS has been associated with a poorer prognosis [81,83]. Furthermore, as stated in an earlier section, CAN is associated with a more significantly depressed BRS [20] and therefore as can be expected a poorer prognosis.…”
Section: Clinical and Prognostic Consequences Of Diminished Brs (Seementioning
confidence: 96%
See 1 more Smart Citation
“…Studies in DM patients have demonstrated that the degree of autonomic (sympathovagal) imbalance determines the extent of BRS impairment [82]. In addition, the extent of BRS impairment is also a determinant factor as a more depressed BRS has been associated with a poorer prognosis [81,83]. Furthermore, as stated in an earlier section, CAN is associated with a more significantly depressed BRS [20] and therefore as can be expected a poorer prognosis.…”
Section: Clinical and Prognostic Consequences Of Diminished Brs (Seementioning
confidence: 96%
“…Female diabetic patients have been shown to have lower BRS and worse prognosis than their male counterparts [81]. Also, there exists a negative correlation between the disease duration and the BRS in diabetic patients [82].…”
Section: Clinical and Prognostic Consequences Of Diminished Brs (Seementioning
confidence: 99%
“…9, 10 It is well-recognized that gender differences exist in the prevalence and levels of these CV diseases and risk factors. [11][12][13][14][15][16][17][18][19][20][21][22] Despite accumulating data, there is still no evidence on how gender influences the effects of exercise training with body weight (BW) loss on hsCRP levels. A meta-analysis study demonstrated the effects of aerobic exercise on CRP, 23 but did not present separate data for exercise-derived CRP lowering in each gender.…”
Section: Subjectsmentioning
confidence: 99%
“…24,25 Further, it has been recently reported that decrease in BRS can predict CV events in Type 2 diabetics. 26,27 Furthermore, it has been documented earlier that decrease in BRS predicts cardiac mortality in myocardial infarction patients. 28,29 Thus, decreased BRS in FDR of Type 2 diabetics as observed in the present study could increase their CV risks and predispose them to adverse CV events.…”
Section: Discussionmentioning
confidence: 95%